2021
DOI: 10.1177/1934578x211044565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enzyme Inhibition and Anti-Quorum Sensing Potentials of Melaleuca alternifolia and Citrus sinensis Essential Oils

Abstract: In this study, Melaleuca alternifolia (Maiden and Betche) Cheel (tea tree) oil and C. sinensis (L.) Osbeck (orange) oil was procured, and their chemical compositions were characterized by gas chromatography coupled with mass spectrometry, with co-injection using authentic samples. The oils were rich in monoterpene hydrocarbons making up 84.5% of C. sinensis and 48.9% of M. alternifolia oils. High amounts of oxygenated monoterpenoids were also identified in C. sinensis (9.6%) and M. alternifolia (49.3%) oils. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The effects of natural products on bacterial biofilm result mostly from the inhibition of exopolymeric matrix formation and the suppression of cell adhesion, thereby disrupting the establishment of the extracellular matrix, reducing virulence factors, and blocking quorum sensing communications and growth of the biofilm [ 56 ]. Several natural compounds have shown antibiofilm and anti-quorum sensing activities, and they are promising antimicrobial substances since, in addition to their activities, the natural products extracts, essential oils, and phytochemicals have high efficacy as biofilm inhibitors and anti-quorum sensing agents with greater chemical stability, small molecular weights, and low toxicity to human health [ 9 , 52 , 57 , 58 , 59 , 60 , 61 ]. The results obtained in this study can be further supported by the fact that various bee products such as honey and propolis have been reported to possess good antimicrobial, antibiofilm, and anti-quorum sensing activities against pathogenic bacteria [ 59 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of natural products on bacterial biofilm result mostly from the inhibition of exopolymeric matrix formation and the suppression of cell adhesion, thereby disrupting the establishment of the extracellular matrix, reducing virulence factors, and blocking quorum sensing communications and growth of the biofilm [ 56 ]. Several natural compounds have shown antibiofilm and anti-quorum sensing activities, and they are promising antimicrobial substances since, in addition to their activities, the natural products extracts, essential oils, and phytochemicals have high efficacy as biofilm inhibitors and anti-quorum sensing agents with greater chemical stability, small molecular weights, and low toxicity to human health [ 9 , 52 , 57 , 58 , 59 , 60 , 61 ]. The results obtained in this study can be further supported by the fact that various bee products such as honey and propolis have been reported to possess good antimicrobial, antibiofilm, and anti-quorum sensing activities against pathogenic bacteria [ 59 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pigment production is one of the easiest evidence of quorum sensing which is measurable. The violet coloration produced by C. violaceum CV12472 is violacein, which is an antioxidant molecule that protects the bacterial membrane from oxidative stress and therefore, inhibiting the production of violacein by the synthesized polymeric gels is beneficial effect that can reduce the virulence of the bacteria 40 . The best violacein inhibition was exhibited by the PSPMA‐DAZ and diazaborine‐based polymers have shown violacein inhibition in previous studies 9 .…”
Section: Resultsmentioning
confidence: 94%
“…This compound is the main one because of its antifungal, antiinflammatory, antimicrobial, and antiviral effects [33]. In a study conducted by Alfred Ngenge [34], regarding tea tree essential oil, it was found that the composition of the main compounds in the oil consisted of terpinene-4-ol (45.6%), γ-terpinene (19.4%), α-terpinene (9.3%), 1,8-cineole (5.2%), terpinolene (3.2%), p-cymene (7.6%), dan α-terpineol (3.5%). In addition, the anti-tyrosinase activity of this oil was also measured and the IC50 was 82.3 ± 0.5 g/mL, smaller than the positive control, kojic acid, which was 23.5 ± 0.3 g/mL.…”
Section: Tea Tree Oilsmentioning
confidence: 99%